Cloud Intelligent Parking Management System Based on Internet of Things Technology. Issue 4 (April 2021) - Yao, Ru; Yang, Jinhua; Liu, Meizhen
Abstract: In recent years, with the rapid development of the national economy, the penetration rate of domestic private cars has risen rapidly. There are too many cars with fewer parking spaces, so many people choose to park their cars on roads. It has caused traffic jams and brought security risks, finally it puts a huge pressure on vehicle management. It requires more parking lots and more effective and convenient parking management and operation methods to improve the service level of parking lots [6]. It is necessary to design an intelligent parking system based on the Internet of Things technology and cloud platform to achieve the highest utilization of space resources and the largest allocation rate of personnel deployment. The intelligent parking lot management system of the Internet of Things is designed and developed to meet the goals of enterprise informatization management and efficient operation and implementation. The web platform conducts the joint operation of users and administrators to realize online reservation, parking at any time, and online payment for car pickup at any time.